Educação ambiental e interdisciplinaridade: da formação inicial à prática pedagógica na educação básica - AVELAR, Marcilene Calandrine de (Universidade Federal do Pará, 2020)
Theinsertion of environmental education (EE) in an interdisciplinary and permanent manner has been a real challenge for the educational system, both in higher and basic education, since the creation of the National Policy of Environmental Education, Law 9795/99. However, attempts have been made over those yearsto fertilize an approach in the theoretical field and its practical implementation, oriented by the contextualization, articulation and resignification of environmental knowledges. Based on this, this research aims to recognize the existence and organization of EE in the curriculum of the PARFOR-Pedagogia-UFPA (National Plan for the Training of Basic Education Teachers, Pedagogy, Federal University of Pará) course and its contributions tothe application of interdisciplinary pedagogical practices at São Miguel Municipal School in Abaetetuba/PA. The theoretical discourse is based on the concepts of EE on the conservationist, pragmatic and critical emancipator macrotrends for understanding the complexity of environmental issues, according to authors Loureiro and Layrargues, Leff, Morin, among other authors who deal with the subject. Regarding the type of research, action research with a qualitative approach was chosen. For data collection, a documentary analysis was first made in the Pedagogical Political Project of the Course (PPC), followed by a questionnaire for 30 teachers/students from the PARFOR-Pedagogia-UFPA, and for the investigation of the pedagogical practice in the basic education, the systematic observation of the pedagogical practices at School. The results were systematized through mental maps and point to a gradual change in the insertion of EE in the higher education curriculum and the conception of the importance of effective interdisciplinary practices in basic education, although there are still gaps throughout the educational process. These findings were fundamental for the elaboration of the research product that consisted of an interactive and interdisciplinary paradidactic book of Environmental Education, elaborated together with two teachers and twenty-two students of themultigrade class of the 4th and 5th grade from elementary school I of São Miguel Municipal School in Abaetetuba/PA. The validation of the paradidactic book was made through a questionnaire applied to the 30 participating teachers/students and another 10 teachers from a municipal school in Ananindeua/PA. The results showed that the book is an interdisciplinary didactic resource, with potential applicability in different contexts and that will enable the student to learn significantly in relation to socio-environmentalissues.